Synthesis of Sn4P3/reduced graphene oxide nanocomposites as highly efficient electrocatalysts for CO2 reduction. Issue 20 (5th October 2020) - Lu, Lu; Guo, Weiwei; Chen, Chunjun; Zhu, Qinggong; Ma, Jun; Wu, Haihong; Yang, Dexin; Yang, Guanying; Sun, Xiaofu; Han, Buxing
Abstract : Sn4 P3 /reduced graphene oxide nanocomposites exhibit high activity and selectivity for CO2 electroreduction to CO. Abstract : Sn4 P3 /reduced graphene oxide nanocomposites exhibited high selectivity for CO over a wide potential range from −2.2 V to −2.5 V vs. Ag/Ag + . The maximum faradaic efficiency for CO can reach 96.6% with a high current density of 68.0 mA cm −2 . The high efficiency and selectivity can be attributed to the modified electronic structure of Sn sites, the small Sn4 P3 nanoparticles and their dense packing in a conductive matrix, leading to a high density of active sites for adsorbing CO2 and stabilizing the CO2 ˙ − intermediate.